2014
DOI: 10.1016/j.ajpath.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

The Onset of Heat-Induced Testicular Calcification in Mice

Abstract: Spermatocytes of MRL/MpJ mice are more heat resistant than those of C57BL/6 mice in experimental cryptorchidism. This phenotype depends in part on the locus at the 81-cM region of MRL/MpJ-type chromosome 1 (Chr 1). To evaluate the function of this locus, we examined pathological changes in mouse testes resulting from transient scrotal heat stress. Immediately after scrotal heat stress, meiosis progression and blood-testis barrier integrity were preserved in MRL/MpJ but not in C57BL/6 mice, nor in a C57BL/6-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Local testicular heat treatment with 43°C water induced reversible oligospermia or azoospermia in rodents and monkeys with increased germ cell apoptosis [ 31 – 36 ], and when the heat treatment stopped after 30 days, the sperm quantity could recover to the original level. The heat treatment of the scrotum was mainly through the impact on the metabolism and apoptosis of spermatogenic cells to decline the fertility of many kinds of animal models; moreover, this impact was temporary and reversible [ 32 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Local testicular heat treatment with 43°C water induced reversible oligospermia or azoospermia in rodents and monkeys with increased germ cell apoptosis [ 31 – 36 ], and when the heat treatment stopped after 30 days, the sperm quantity could recover to the original level. The heat treatment of the scrotum was mainly through the impact on the metabolism and apoptosis of spermatogenic cells to decline the fertility of many kinds of animal models; moreover, this impact was temporary and reversible [ 32 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that the autoimmune disease models, MRL/MpJ and their mutant strain MRL/MpJ- Fas lpr/lpr mice, have unique phenotypes in the reproductive organs, such as metaphase-specific apoptosis of meiotic spermatocytes [ 11 13 ], heat shock resistance of spermatocytes found in experimental cryptorchidism [ 14 , 15 ], testicular calcification after transient scrotal heat stress [ 16 , 17 ], existence of testicular oocytes in newborn males [ 18 , 19 ], and development of ovarian cysts originating from the rete ovarii [ 20 ]. In addition, female MRL/MpJ- Fas lpr/lpr mice show abnormal reproductive processes [ 21 , 22 ], indicating that these mouse strains are useful models for reproductive immunology.…”
Section: Introductionmentioning
confidence: 99%